DIVERSIFICATION NOODLE PRODUCTS BASED ON CORN FLOUR FOR MAKING SOY SAUCE CHICKEN IFUMIE - Ichda Chayati, Krisna Mona Fitria (Prosiding Pendidikan Teknik Boga Busana, 2020)
Indonesia country dependent on imports of food raw materials to meet the needs of masayrakat require appropriate solutions in the processing of local materials. One way to reduce such imports, namely the manufacture and utilization of local raw materials such as replacing flour with corn kernels into flour processing and manufacturing of products using corn flour. This study uses the R & D (Research and Development) with four stages: define, design, develop, disseminate. This study aims to 1) find the right recipe ifumie corn, 2) determine public acceptance of product acceptance ifumie corn, and 3) determine the nutrient content in corn ifumie. The results obtained show that every 100gram ifumie has a water content of 4.39%, ash content ifumie by 0, 95%, amounting to 9.46% protein content, fat content of 23.88%, 11.30% of crude fiber and carbohydrate content of 448.35 cal. From some of the test results Ifumie Chicken Soy product manufacturing showed a positive response so that products can be accepted by society. Keywords: ifumie, corn flour, wheat flour